Determining the effect of the addiction awareness program on substance addiction awareness and tendency to use substances levels - Gulen, Salih; Dogan, Ufuk (Taylor & Francis Inc, 2024)
The study aimed to increase the substance use tendency and substance addiction awareness levels of 9th and 10(th)-grade students with the Addiction Awareness Program (AAP). The experimental method was used in the research, and the AAP applied in the study was completed in 10 weeks. The research was formulated for secondary school students and, thus, was conducted with 230 9th and 10(th)-grade participants studying at a provincial secondary school in Mus, Turkey. The AAP training decreased the substance use tendency levels of secondary school students and increased their awareness of substance addiction. Due to the AAP's implementation, there was also an increase in the substance addiction awareness scores of secondary school students who did not tend to use substances.
Keywords: Secondary school students; substance addiction; substance addiction awareness; substance use tendency; addiction awareness program